2011
DOI: 10.1111/j.1574-6941.2011.01041.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of endochitinase-transformed white spruce on soil fungal communities under greenhouse conditions

Abstract: Chitinase genes isolated from plants, bacteria or fungi have been widely used in genetic engineering to enhance the resistance of crops and trees to fungal pathogens. However, there are concerns about the possible effect of chitinase-transformed plants on nontarget fungi. This study aimed at evaluating the impact of endochitinase-transformed white spruce on soil fungal communities. Endochitinase-expressing white spruce and untransformed controls were transplanted in soils from two natural forests and grown for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 52 publications
1
8
0
Order By: Relevance
“…This demonstrates that for these EM fungal species, the transgenic chestnut does not appear to have any nontarget impacts. The result is consistent with studies that have demonstrated minimal to no impact on EM fungi by a number of transgenic tree species expressing a variety of transgenes (48)(49)(50)(51)(52). One such study, on a transgenic American elm expressing an antimicrobial peptide to improve Dutch elm disease resistance, found that there was no significant difference in mycorrhizal colonization during the field trial (53).…”
Section: Discussionsupporting
confidence: 75%
“…This demonstrates that for these EM fungal species, the transgenic chestnut does not appear to have any nontarget impacts. The result is consistent with studies that have demonstrated minimal to no impact on EM fungi by a number of transgenic tree species expressing a variety of transgenes (48)(49)(50)(51)(52). One such study, on a transgenic American elm expressing an antimicrobial peptide to improve Dutch elm disease resistance, found that there was no significant difference in mycorrhizal colonization during the field trial (53).…”
Section: Discussionsupporting
confidence: 75%
“…When data from all sampling dates were considered together, Lottmann et al (2010) found few statistical differences in the microbial communities associated with GM and control trees, which suggested that there was no significant impact of this genetic modification on rhizosphere microbial communities. Lamarche et al (2011) did not detect any significant differences in soil fungal biomass, diversity or community structure caused by white spruce that constitutively expressed the ech42 gene. By contrast, Andreote et al (2009) detected differences between bacterial communities, not only between transgenic and non-transgenic eucalyptus (Eucalyptus robusta Smith), but also among wild-type plants.…”
Section: Discussionmentioning
confidence: 54%
“…1). Sugiyamaella paludigena originally was isolated from high moor peat near Moscow, Russia (Golubev et al 1981), and more recently it was reported from rhizosphere soil of white spruce (Lamarche et al 2011). Sugiyamaella lignohabitans first was described from a decaying log of paper birch and associated insect frass in USA (Kurtzman 2007).…”
Section: Resultsmentioning
confidence: 99%